(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kandito A, Hartono S, Sulandari S, Somowiyarjo S, Widyasari YA. 2019. First report of naturally occurring recombinant non-coding DNA satellite associated with Tomato yellow leaf curl Kanchanaburi virus on eggplant in Indonesia. Biodiversitas 20: 129-136. Begomovirus is a viral genus which is a major impediment in the cultivation of plants, especially Solanaceae. Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV) is a member of the Begomovirus genus that is widely reported to infect eggplant and results in severe symptoms of chlorosis. In addition to the type of virus that infects, the severity of symptoms can also be caused by the presence of betasatellite associated with several begomovirus species. The presence of betasatellite that is related to several begomovirus species can lead to more severe symptoms. The aim of this study was to identify satellites associated with begomovirus in Indonesia. Eggplant samples from Bantul, Special Region of Yogyakarta show with mosaic and severe chlorotic symptoms due to Begomovirus infection. Total DNA samples were subject to PCR amplification using universal primer for begomovirus PALIV1978/PAR1C715 and specific primer for betasatellite ?01/?02. The PCR amplification produced a DNA band measuring ± 1600bp, identical size of begomovirus. The amplification of the betasatellite specific primer produced a DNA band featuring ± 1300bp, identical size of betasatellites that were associated with begomovirus in the sample. The results of DNA sequencing, suggested that begomovirus in this study had a close relationship with TYLCKaV from Thailand and Indonesia. Characterization of the satellite-based on nucleotide sequence revealed the presence of stem-loop structures, satellite conservative regions, and adenine-rich regions that resembled structures present in the betasatellite, which were associated with Tomato leaf curl virus and Ageratum yellow vein virus, with no ORF found. These results indicated that the TYLCKaV could be associated with a non-coding satellite. This result is the first report regarding the TYLCKaV association with a non-coding satellite in Indonesia.